Generation Z’s awareness of eating at halal certified restaurants - Kamarulzaman, Nitty Hirawaty; Ahmad Tarmizi, Hazwani; Misri, Syamim Mahirah (HH Publisher, 2020)
Halal food indeed remains the main concern among consumers when they decide to eat outside. As there are many different approaches in choosing a restaurant among consumers especially youngsters, the halal status of these restaurants usually raises some critical issues particularly on ingredients used as well as halal certification and logo. Hence, this study was carried out to investigate the level of awareness among Generation Z (Gen Z) towards eating at halal certified restaurants, to examine the association between socio-demographic profiles of Gen Z and level of awareness towards eating at halal certified restaurants and to determine factors that influence Gen Z towards eating at halal certified restaurants. Data was gathered via self-administered questionnaires with 1,050 Gen Z respondents. Descriptive analysis, mean score analysis, Chi-square analysis, and factor analysis were used to analyze the data. The results revealed that a low level of awareness was found among Gen Z towards eating at halal certified restaurants. The results also showed a few socio-demographic profiles to have associations with the awareness level towards eating at halal certified restaurants. Five factors were revealed to influence Gen Z towards eating at halal certified restaurants namely halal certification and logo, religious responsibility, lifestyle, social influence, and attitude. As the level of awareness among Gen Z towards eating at halal certified restaurants was found to be low thus, relevant awareness programs and halal campaigns should be carried out more frequently to increase their level of awareness on halal.